Integrasi Lintas Media dalam Proses Kencan Daring: Studi Kasus Pengguna Tinder dan Bumble di Kalangan Mahasiswa Jakarta: Penelitian - Annisa Putri; Frisky Freny Matahari; Amir Machmud; Ranji Primarianda; Ronald H.P.; Siti Suhanah Wati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the patterns of dating app usage through the lens of Cross Media theory, focusing on the integration of multiple digital platforms in the partner-seeking process. Employing a qualitative case study approach, data were collected through in-depth interviews with three key informants who actively use dating apps such as Tinder, Bumble, Tantan, and Line People Nearby. The results reveal a concrete pattern of cross-media transition: all three informants reported moving from Tinder to Instagram before proceeding to WhatsApp as a strategy for identity verification and creating a sense of comfort before offline meetings. Additional findings highlight user preferences for specific apps; for example, Bumble is perceived as more exclusive and empowering for women, while Tinder is seen as more casual but sometimes overly suggestive. The discussion emphasizes that integrating dating apps with other social media platforms plays a crucial role in building trust, reducing the risk of fraud, and providing a safer space for identity verification. This study highlights the significance of cross-media literacy in online relationship-building and emphasizes the importance of digital literacy in safeguarding privacy and security within the evolving digital dating ecosystem.